Asymmetry of cardiac [123I] meta-iodobenzyl-guanidine scans in patients with ventricular tachycardia and a "clinically normal" heart. Issue 1 (January 1993) - Gill, J S; Hunter, G J; Gane, J; Ward, D E; Camm, A J
Abstract : OBJECTIVE--Patients with exercise induced ventricular tachycardia associated with a "clinically normal" heart may have an abnormality of the regional distribution of the cardiac sympathetic nerve supply. In this study the regional distribution of the myocardial nerve supply in patients with ventricular tachycardia (VT) and control subjects was examined by [123] meta-iodobenzylguanidine (MIBG) scanning. PATIENTS AND DESIGN--Eight patients with exercise induced VT and seven patients with VT unrelated to exercise with "clinically normal" hearts were studied and compared with a control group of six subjects with atrioventricular reentrant tachycardia not related to exercise and eight patients with angiographically normal left ventricular function and normal coronary anatomy who had thallium scans without evidence of ischaemia or fixed perfusion deficits. METHODS--Single photon emission computed tomography gamma scanning was performed in patients three hours after intravenous injection of MIBG. The left ventricular MIBG uptake data was processed into bull's-eye target plots. The inferior portion of the scan frequently showed artefact due to uptake of MIBG in the liver or spleen and was not used for statistical analysis. Asymmetry of uptake was defined as a ratio of uptake exceeding 1.25 in the upper quadrants (posterior (anterolateral free wall)/anterior (anteroseptal region)) of the MIBG scan. RESULTS--Patients with VT had a higher proportion of asymmetrical MIBG scans (47%) than subjects in the control groups (0%) and this was particularly obvious in the patients with exercise induced VT (62.5%). This suggests that patients with VT may have relative denervation in the septal portion of the left ventricle leading to an imbalance of the sympathetic supply to the myocardium and locally imbalanced sympathetic or parasympathetic interactions. Considerable evidence from animal experiments suggests that imbalance of the sympathetic supply to the myocardium is important in the genesis of ventricular arrhythmia. CONCLUSIONS--These results support the hypothesis that selective denervation of the human myocardium may be an important mechanism in the genesis of VT in "clinically normal" hearts.